2016
DOI: 10.17116/jnevro20161168217-23
|View full text |Cite
|
Sign up to set email alerts
|

The role of ATP-dependent potassium channels and nitric oxide system in the neuroprotective effect of preconditioning

Abstract: The neuroprotective effect of preconditioning is caused by the activation of K+ATP channels. An analysis of NO metabolite concentrations in the blood of rats with IP suggests that Hb-NO complexes belonging to R-conformers deposit and carry NO in tissues releasing NO accumulated via R→T transfer in conditions of ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Ischemic infarction in the fronto-parietal region of cerebral cortex was induced by electrocoagulation of the distal branch of left MCA and the adjacent vein, with simultaneous ligation of the ipsilateral carotid artery. This model of ischemic stroke was chosen because of its good reproducibility in experiments which demonstrated a 30–45% decrease of necrotic area after IP or PhP (Samoilenkova et al, 2007 ; Deryagin et al, 2016 ). The MCA coagulation altitude was chosen so that necrosis developed mainly in the frontoparietal cortex, without affecting subcortical structures, thereby avoiding complications of visceral functions and animal death.…”
Section: Methodsmentioning
confidence: 99%
“…Ischemic infarction in the fronto-parietal region of cerebral cortex was induced by electrocoagulation of the distal branch of left MCA and the adjacent vein, with simultaneous ligation of the ipsilateral carotid artery. This model of ischemic stroke was chosen because of its good reproducibility in experiments which demonstrated a 30–45% decrease of necrotic area after IP or PhP (Samoilenkova et al, 2007 ; Deryagin et al, 2016 ). The MCA coagulation altitude was chosen so that necrosis developed mainly in the frontoparietal cortex, without affecting subcortical structures, thereby avoiding complications of visceral functions and animal death.…”
Section: Methodsmentioning
confidence: 99%
“…It can damage nerve cells and increase cell membrane permeability, leading to brain edema and postoperative cognitive dysfunction [21,22]. Several previous studies have suggested that mitochondrial ATP-sensitive potassium channels play an important role in this process [23][24][25]. Brain edema and nerve tissue degeneration may indicate cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimmune molecular responses linked to conditioning include innate immune signaling pathways such as Toll-like receptors (TLRs) and type 1 interferons (122). Intracellularly, many kinases and signaling factors known to be important in smooth muscles have been identified, including heme oxygenase-1, nitric oxide (NO), HIF, VEGF, ATPsensitive K ϩ (K ATP ) channels, prostaglandins, bradykinin, PKC, PKG, and ROS as well as stromal derived factor-1␣ and microRNA-144 (3,25,44,45,85,132,150,202).…”
Section: Current Synthesismentioning
confidence: 99%